Antimicrobial activity, phytochemical analysis and toxicity test of Cosmos caudatus Kunth extract - Mohamed Yusoff, Nor Asma Husna (2015)
The uses of natural products in the elimination of microorganism contaminations in food have increased nowadays. In this study, air-dried leaf methanolic extract of Cosmos caudatus Kunth was used. The antimicrobial activity of C. caudatus extract and time-kill curve analysis was evaluated against foodborne pathogens. The stability of extract at different pH and temperature also were evaluated. The identification and quantification of bioactive compounds were conducted using LC-MS/MS and HPLC. Three representative microorganisms were observed under transmission electron microscope (TEM). The effect of C. caudatus extract on natural microflora in selected food materials and its sensory acceptability were tested at different concentrations of extract for different exposure time. The toxicity level of extract was assessed using Artemia salina spp. Results showed that all tested foodborne pathogens were susceptible to C. caudatus extract at different range of MIC value from 6.25 to 50.00 mg/ml. Time-kill curve study shows that all tested foodborne pathogens can be killed by the extract with different time-killing curve. Generally, the antimicrobial activities of C. caudatus extract were not significantly affected on tested pH and temperatures. LC-MS/MS analysis identified the presence of rutin, quercetin 3-O-glucoside, quercetin 3-O-arabinoside, quercetin 3-O-rhamnoside and quercetin. HPLC analysis showed the highest concentration was quercetin rhamnoside (29.66 mg/g). All the identified active compounds proved possess antimicrobial activities. TEM observation showed changing on the pathogen cells’s structure. Generally the significant reduction of natural microflora in raw food materials were started at 0.05% of C. caudatus extract for 10 min of exposure time, and the sensory acceptability at this concentration and time were accepted by the panellists. The toxicity study demonstrated that C. caudatus extract was not toxic to A. salina (LC50 = 3.54 mg/ml). In conclusion, C. caudatus extract exhibits antimicrobial activities, thus can be developed as natural sanitizer for washing raw food materials.